1997
DOI: 10.1021/jf9607573
|View full text |Cite
|
Sign up to set email alerts
|

Method for Estimation of Proanthocyanidins Based on Their Acid Depolymerization in the Presence of Nucleophiles

Abstract: Depolymerization of proanthocyanidins in the presence of phloroglucinol or benzyl mercaptan nucleophiles was studied to develop a method for their quantitative determination. Degradation products were separated and quantified by either GC or HPLC and the reaction conditions optimized. The high depolymerization yields obtained with benzyl mercaptan make the method suitable for proanthocyanidin determination. The method is more specific and sensitive than the colorimetric methods classically used. It is particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 30 publications
8
146
0
Order By: Relevance
“…Benzyl mercaptan was obtained from Aldrich. Thioether standards were prepared as previously described (Matthews et al, 1997), and standard spectra (UV, mass, 1 H NMR) were consistent with previous data (Prieur et al, 1994;Matthews et al, 1997).…”
Section: Chemicalsmentioning
confidence: 92%
See 2 more Smart Citations
“…Benzyl mercaptan was obtained from Aldrich. Thioether standards were prepared as previously described (Matthews et al, 1997), and standard spectra (UV, mass, 1 H NMR) were consistent with previous data (Prieur et al, 1994;Matthews et al, 1997).…”
Section: Chemicalsmentioning
confidence: 92%
“…Amount and composition. The quantity of extracted procyanidins per berry was determined by acid-catalyzed degradation in the presence of benzyl mercaptan (thiolysis) (Rigaud et al, 1993;Matthews et al, 1997). The quantities of extracted material declined from a high value at ve raison ( Fig.…”
Section: Procyanidinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds can be considered polymers of flavonoids such as catechins, and in leaves and bark, they can represent up to 40% of the dry weight (Kuiters 1990;Matthews et al 1997). The biodegradation of tannins to CO 2 (mineralization) may be the ratelimiting step in recycling biological C (Lattanzio et al 2008).…”
Section: Soil (Bio)activities and Nutrient Cycles Within The Rhizospherementioning
confidence: 99%
“…However, an analytical method using acid depolymerization with nucleophilic agents has been developed, and it enabled us to determine the subunit composition and mean degree of polymerization (mDP) of proanthocyanidins and to evaluate their influence on the extraction of proanthocyanidins during maceration. 9,10) Analyses using this method revealed that skin proanthocyanidins differ from seed proanthocyanidins by the presence of prodelphinidins, their higher mDP, and their lower proportion of galloylated subunits. 1,7,9,11) These differences are expected to be the reason for their organoleptic differences.…”
mentioning
confidence: 99%